Disenfranchisement of convicted adult citizens: comparative and international human rights perspectives - Ziegler, R (2009)
This thesis analyses the appropriateness of disenfranchising convicted adult citizens from comparative and international human rights perspectives. Chapter One explores the transition from direct democracy to representative government, and the subsequent increased importance of elections. It highlights the paradigm shift that the perception of voting has undergone, from being seen as a privilege, granted to a handful of society members, to being viewed as an entitlement. Today, electoral systems are commonly based on universal suffrage, and voting eligibility is normally qualified by (only) two criteria: community membership and competence. It is suggested that these criteria should be used for scrutinising convicts’ disenfranchisement. Chapter Two traces the transformation that the treatment of convicts underwent, with notions of forfeiture of rights and ‘civil death’ gradually giving way to ideas of 'residual liberty' and of convicts as rights-holders. Subsequently, regulatory and penal justifications for convicts' disenfranchisement are assessed. The analysis concludes that disenfranchisement should be classified as a form of punishment, and that, due to its adverse effects on individuals as well as collectives disenfranchisement should cease to be imposed. Chapter Three offers comparative perspectives on current challenges to disenfranchisement legislation. It examines American disenfranchisement jurisprudence alongside recent judgments from Canada, South Africa, the European Court of Human Rights and Australia. It is concluded that the non-American judgments exhibit an identifiable global trend towards enfranchising (some) convicts which can be partially attributed to a transnational judicial discourse. Chapter Four examines the human rights treaty regime's perspective. Interpreting Article 25 of the International Covenant on Civil and Political Rights which guarantees the right-to-vote, it is posited that the provision does not proscribe disenfranchisement as such. Rather, disenfranchisement is subjected to balancing/proportionality analysis. Building on Chapter Two's normative contentions, and on the notion that voting eligibility constitutes the essence of the right-to-vote, the thesis advocates the adoption of an optional protocol to the ICCPR proscribing disenfranchisement. It is submitted that the facilitative nature of the right-to-vote makes it less vulnerable to cultural relativity, deference and margin of appreciation objections. Analogies are drawn between the proposed protocol and the Optional Protocol to the ICCPR Aiming at the Abolition of the Death Penalty.